IMMUNOGENIC ACTIVITY OF LIPOPOLYSACCHARIDES FROM PASTEURELLA MULTOCIDA IN RABBITS - A. Ashraf; S. Mahboob; K. Al-Ghanim; T. Huma; M. S. Shah (Journal of Animal and Plant Sciences, 2014)
Lipopolysaccharides (LPS) were extracted from the whole cell of the causative organism (Pasteurella multocida) and quantified by using the semi-carbazide method. This quantified antigen was then inoculated subcutaneously into rabbits to stimulate antibody production. The maximum antibody titre was determined by applying indirect ELISA, and was found to have been achieved at one week post inoculation in all groups. It was concluded that with an increase in the dose of LPS antigen, the antibody titre increased and the combination of LPS of P. multocida with yeast produced more immunity when compared to LPS alone in rabbits.
Keywords: Haemorrhagic septicaemia; Immunity; LPS; ELISA Pasteurella multocida